Limited and inconclusive effects of computer-based neurocognitive training on PTSD, comorbid depression and executive functioning: a systematic review and meta-analysis - Patric Muschner; Lena Goldschmidt; Luisa Sophie Gröning; Gerd-Dieter Willmund; Martina Piefke (Frontiers in Psychology)
Patients with posttraumatic stress disorder (PTSD) and comorbid depression often experience neurocognitive deficits. While computer-based neurocognitive training (c-bnt) has shown benefits in primary depression, its efficacy for PTSD remains unclear. This meta-analysis evaluated the impact of c-bnt on PTSD severity, comorbid depression, and neurocognitive functions. A systematic review following PRISMA guidelines was conducted across databases (PsycINFO, PubMed, Scopus, PubPsych) from February to June 2025, focusing on randomized controlled trials (RCTs) involving PTSD and c-bnt. Bias risk was assessed using the revised Cochrane Risk-of-Bias Tool, and effect sizes were calculated with Cohen’s d. Heterogeneity was measured using I2. The review, registered with PROSPERO (CRD42023444417), included eight studies, with five providing meta-analyses data (n = 221). Although c-bnt led to a small reduction (d = −0.21) on PTSD symptoms, this effect was not statistically significant (p = 0.31). Comorbid depression showed inconsistent improvements, with no significant overall effect (d = −0.10). A systematic review of neurocognitive functions, covering six studies (n = 220), showed mixed results for cognitive flexibility and working memory, but no significant improvements in inhibition. These findings suggest that c-bnt may contribute to reductions in PTSD symptoms and potentially benefit comorbid depression and neurocognitive functions, particularly working memory and cognitive flexibility. However, the small number of studies, moderate heterogeneity, and methodological diversity highlight the need for further research. C-bnt is a potentially promising, cost-effective treatment that warrants exploration as an adjunctive therapy for PTSD.